The global transformations reader: an introduction to the globalization debate. 2nd ed. (Cambridge, 2005)
This revised & updated edition brings together the most original contributions from both sides of the globalization debate. Extensive new material incorporates the latest developments & sets the issues in the context of a global order in constant flux.